SYNTHESIS AND CHARACTERIZATION OF MgO-Cr2O3-ZTA CUTTING TOOL MATERIAL - Ahmad Azhar, Ahmad Zahirani (2013)
The effect of MgO and Cr2O3 addition on the microstructure and mechanical properties of ZTA ceramic composite were investigated in this study. Various amounts of MgO and Cr2O3 were added into ZTA separately. The starting materials was mixed continuously for 8 hours and subsequently hydraulically pressed at 300 MPa. The pressed samples were sintered at 1600 oC for 4 hours. There are three parts in this study. The first part consists of addition of MgO into ZTA. Second part is focused on the effect of MgO particles sizes on ZTA mechanical properties and the third part is focused on the effect of adding Cr2O3 on ZTA and ZTA-20 nm MgO. For the first part, the results show that an addition of 0.7 wt % of 100 nm MgO produces the highest Vickers hardness (1710 HV). The fracture toughness decreased gradually from 5.93 MPa.m1/2 to 3.79 MPa.m1/2 with further addition of 1.0 MgO wt %. MgO solid solubility in ZTA was determined around 203 ppm. No new mechanism was found with the addition of MgO into ZTA. Microstructural observations show that the NL value for grain size is significantly dependent on the amount of MgO addition. The NL value increase from 0.68 grains/μm to 2.21 grains/μm with the addition of 0.7 wt % of 100 nm MgO. The increase of hardness is due to the small grain size of Al2O3 which is caused by the microstructure pinning effect by MgO. In tool wear measurement, an improvement of 30 % is shown for ZTA sample with 0.3 MgO wt %. For the second part, the particle sizes of MgO were varied from 20 nm to 7000 nm. It was observed that finer size of MgO enhances the microstructure pinning effect; a feature introduce by MgO. ZTA samples with additives of 20 nm of MgO were found to have fine Al2O3 grain size (2.50 grains/μm) compared to ZTA with 100 nm MgO (2.21 grains/μm), 500 nm MgO (1.27 grains/μm) and 7000 nm MgO (0.81 grains/μm). The fine grain of ZTA with 20 nm MgO leads to a high Vickers hardness (1740 HV) but a fracture toughness of 3.62 MPa.m1/2. Formation of MgAl2O4 was detected at different composition of each MgO particle sizes, whereas 1.1 wt % for 20 nm MgO, 0.7 wt % for 100 nm MgO, 0.6 wt % for 500 nm MgO and 0.5 wt % for 7000 nm MgO. Tool wear measurement indicated that ZTA samples with 20 nm MgO shows an increase of 54.8 % compare to ZTA samples with 100 nm MgO. For the third part of the study, amounts from 0 xxv wt % - 1.0 wt % of Cr2O3 are introduced into two separate systems: ZTA and ZTA with 20 nm 1.1 wt % MgO. ZTA samples with the addition of 0.6 wt % of Cr2O3 produced Vickers hardness of 1683HV and fracture toughness of 7.05 MPa.m1/2. The increase of Vickers hardness is attributed to the addition of Cr2O3, which has higher hardness than ZTA. The increase of fracture toughness is due to the large Al2O3 grain and the loss of monoclinic phase inside YSZ due to the presence of Cr2O3. According to XRD analysis, no new phase was formed with the addition of Cr2O3 since both Cr2O3 and Al2O3 are in complete solid solubility with each other. NL values for ZTA samples decrease with the addition of 0.6 wt % Cr2O3 from 1.30 grains/μm to 0.78 grains/μm. Sample of ZTA-20 nm MgO-Cr2O3 has higher Vickers hardness (1693HV) and lower tool wear (0.015 mm2) compared to ZTA-Cr2O3 (1683 HV and 0.0190 mm2). Result of tool wear measurement shows that sample of ZTA-20 nm MgO-Cr2O3 has 35 % of improvement compare to ZTA-Cr2O3. In overall, samples of ZTA-1.1 wt % 20 nm MgO-0.6 wt % Cr2O3 is the best composition for cutting insert application.